Resource integration and co-creation: A customer journey approach - Jesus, Cátia; Alves, Helena (The Routledge Handbook of Service Research Insights and Ideas, 2020)
Value co-creation has been a central point for service researchers, giving rise to countless publications and perspectives on the subject. However, the perspectives dealing with understanding consumer roles and involvement in the co-creation process are not particularly incisive. Therefore, this chapter addresses resource integration, using a cultural event to provide an example context for all direct/indirect interactions between actors and events involved in the value co-creation process. It aims for detailed understanding of how and what types of resources consumers integrate throughout their customer journeys; it also analyzes how this integration influences their experiences at the event. An exploratory and interpretative approach was chosen, based on a case study of the Óbidos Christmas Town event, with the methodological objective of using the customer journey map. In data collection, a semi-structured interview technique was applied to 18 consumers attending the annual event in 2016. The results revealed that certain elements and touchpoints are fundamental to consumers, who use their resources in the co-creation process. Distinct types of behaviour are observed because consumers use different combinations of operant (cultural, physical, and social) and operand resources (monetary resources and tangible goods), based on what they value. Furthermore, all of the direct/indirect interactions between actors and touchpoints at the event result in the integration of resources and fundamental processes of value co-creation. By taking these factors into consideration, organizations can manage to produce better results through the various phases of the consumer experience, in terms of using innovations and producing consumer satisfaction. This chapter addresses resource integration (RI), using a cultural event to provide an example context for all direct/indirect interactions between actors and events involved in the value co-creation process. It presents a brief review of the literature on key topics. The chapter focuses on facilitators of the service ecosystem, including information, knowledge, values, skills, physical products, brands, experimental laboratories, and natural resources. RI is a key mechanism in value creation and a process that is exclusive to each actor. Consumers possess a great variety of operant resources they can use and integrate in co-operative relations with organizations to satisfy their needs and fulfil projects. The actor who becomes involved in developing a service, to provide a new value proposition, has the function of initiator. The initiator begins with an invitation to co-create; after the service is developed, the actor supplying value is a provider and the actor receiving value is a beneficiary.